Psikoanalisis Sigmund Freud dan Implikasinya Dalam Pendidikan - Risydah Fadilah; Ahyar Harundin Sagala; Alvinal Khairani (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Psychoanalytic theory is a theory that seeks to explain the nature and development of human personality. The elements that are prioritized in this theory are motivation, emotions and other internal aspects. This theory assumes that personality develops when there are conflicts from these psychological aspects, which generally occur in children or at an early age. Psychoanalysis has a lot to offer education. The relationship between them is like a marriage in which both partners are aware of their mutual needs, but do not really understand each other and therefore do not understand their name together. So the stated educational goals based on psychoanalytic analysis are to provide guidance for educators and students about what to achieve, the activities they carry out, and about the progress achieved by students.